2018
DOI: 10.1182/blood-2018-99-115362
|View full text |Cite
|
Sign up to set email alerts
|

PRM-151 in Myelofibrosis: Efficacy and Safety in an Open Label Extension Study

Abstract: Introduction: PRM-151, a recombinant human pentraxin-2 molecule, has been shown to prevent and reverse fibrosis in animal models of myelofibrosis (MF) by postulated targeting differentiation of fibrocytes (essential cells in fibrotic process) from monocytes. In the first stage of a two-stage trial, 27 patients (pts) with primary myelofibrosis (PMF), post-essential thrombocythemia/polycythemia vera (post-ET/PV) MF, and Grade 2 or 3 bone marrow fibrosis (BMF) received PRM-151 10 mg/kg IV ± ruxolitinib (RUX) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Furthermore, more studies on transplant strategies and timing are needed, especially with respect to the incorporation of ruxolitinib within the transplant setting, whereas results from comparative studies of transplant and nontransplant approaches are awaited. Finally, as new targeted agents become increasingly available, mutational information may allow more personalized/tailored therapy for patients with myelofibrosis …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more studies on transplant strategies and timing are needed, especially with respect to the incorporation of ruxolitinib within the transplant setting, whereas results from comparative studies of transplant and nontransplant approaches are awaited. Finally, as new targeted agents become increasingly available, mutational information may allow more personalized/tailored therapy for patients with myelofibrosis …”
Section: Discussionmentioning
confidence: 99%
“…Observations of 18 patients with MF who had received treatment comprising ruxolitinib combined with PRM-151 for a median of 31 months showed that the two-drug combination was well tolerated. An overall improvement in BM reticulin and collagen fibrosis grade, as well as reductions in symptoms (MPN-SAF TSS) and palpable splenomegaly were noted [78]. In another trial, 13 of 27 patients (with or without ruxolitinib) have completed at least 72 weeks.…”
Section: Continuously Updated Combination Trials Are Expectedmentioning
confidence: 96%
“…Favorable impacts on spleen size and disease-related symptoms and improvement in bone marrow fibrosis were noted in combination with acceptable tolerability. Despite encouraging preliminary results, the future development of PRM-151 in MF is uncertain [ 136 ].…”
Section: Novel Combinations With Clinical Experiencementioning
confidence: 99%